Deux usages du Psaume 96 - Gosse, Bernard (Old Testament Essays, 1999)
A comparison between Psalm 96, 1 Chronicles 16 and Isaiah 56-59 reveals remarkable parallels. It appears that Psalm 96 was quoted in both Isaiah and Chronicles, but with two different objectives since the perspective on the salvation of Yahweh shifted between the time of Trito-Isaiah and Chronicles.
free
Keywords: 1 Chronicles 16; Christianity; Chronicles I 16; Isaiah 56-59; Psalm 96